1979
DOI: 10.1002/ijch.197900036
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Structure and Complexation, XLVIII Alkali and Alkaline Earth Metal Ion Complexes of Bipyridine, Phenanthroline and Terpyridine

Abstract: Crystalline alkali and alkaline earth metal ion complexes of 2,2′‐bipyridine and 2,2′:6′,2″‐terpyridine are obtained and compared with known and new alkali and alkaline earth metal salt complexes of 1, 10‐phenanthroline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…[43,44]). Lithium thiocyanate or chloride complexes with phen or bpy, of 1:1 stoichiometry, and a 1:2 sodium thiocyanate complex with phen, obtained as hydrates, have later been reported, but not structurally characterized [45]. Phen been studied over many years as ionophores for alkali metal ions for use in ion-selective electrodes and fluorimetry [46], while NMR and vibrational spectroscopic studies of adducts of phen or bpy with group 1 salts have also been carried out [47Ϫ50].…”
Section: Introductionmentioning
confidence: 99%
“…[43,44]). Lithium thiocyanate or chloride complexes with phen or bpy, of 1:1 stoichiometry, and a 1:2 sodium thiocyanate complex with phen, obtained as hydrates, have later been reported, but not structurally characterized [45]. Phen been studied over many years as ionophores for alkali metal ions for use in ion-selective electrodes and fluorimetry [46], while NMR and vibrational spectroscopic studies of adducts of phen or bpy with group 1 salts have also been carried out [47Ϫ50].…”
Section: Introductionmentioning
confidence: 99%
“…117 It was suggested that the [M (tpy) 2 ] 2• diradical complexes possessed S 4 -symmetry; however, further insight into the structure of these complexes was not given by these authors. The same basically holds true for the assemblies Mg(NO 3 ) 101 Moreover, Emara et al gave evidence for the formation of a reasonably stable Mg II -tpy complex of 1 : 1 stoichiometry in water (K = 5.858 ± 0.023 mol −1 ). 118,119 Notably, Be II complexes with bidentate polypyridyl ligands were already reported in the early 1960s.…”
Section: Terpyridine Complexes Of Alkaline Earth-metal Ions (Group 2)mentioning
confidence: 57%
“…These results are in line with those made earlier by Vögtle et al, who combined Li(SCN) or Na (SCN) with tpy in solution. 101 These authors performed 23 Na NMR titration studies to qualitatively show the formation of the [Na(tpy)] + species. According to Shamsipur et al, the lg K 1 value for [Na(tpy)] + in MeNO 2 solution was 1.67, thus significantly lower as for [Li(tpy)] + (lg K 1 = 3.24).…”
Section: Terpyridine Complexes Of Alkalimetal Ions (Group 1)mentioning
confidence: 99%
See 2 more Smart Citations